Incidental gallbladder carcinoma post-cholecystectomy: Diagnostic dilemma and therapeutic implications - Sufi Sumsul Yeaman; Mohamed Arif Hameed Sultan; Jahidul Islam Khan; Md. Safiqul Islam; Arjun Deb (Authorea, 2025)
Gallbladder carcinoma is a rare but aggressive malignancy that poses significant diagnostic and therapeutic challenges. The clinical examination of a patient with suspected gallbladder pathology often reveals critical insights into the underlying condition. In this case, the patient presents with an ill-looking, undernourished appearance, accompanied by vital signs indicating a stable yet concerning state: a pulse of 78 bpm, blood pressure of 110/75 mmHg, and a respiratory rate of 12 breaths per minute, with no fever noted. A notable finding during the abdominal examination is the presence of a firm, tender, palpable mass in the right hypochondrium, indicative of a gallbladder abnormality that moves with respiration. Given these clinical observations, differential diagnoses must be meticulously considered, including cholelithiasis, empyema of the gallbladder, gallbladder carcinoma, and cholangiocarcinoma.